Medication reconciliation in pediatric patients with cancer at Brazilian public hospital - Nathalia S. PENHA; Marcos V. SILVA; Mayara A. BARROS; Tácio M. LIMA (Sociedade Brasileira de Farmácia Hospitalar e Serviços de Saúde, 2020)
Objective: This study aims to describe the discrepancies found through medication reconciliation performed by a clinical pharmacist in pediatric patients admitted to an oncology public hospital. Methods: A descriptive cross-sectional study was carried out in a North Brazilian oncology public hospital. Patients aged 0 - 19 years old with any cancer diagnosis and/or stage were interviewed by a clinical pharmacist within 24 hours of hospital admission about their current medication use in order to develop an updated list to be compared with the medical prescription. Medication discrepancies were classified according the medication discrepancy taxonomy (MedTax). Results: One hundred and sixty-seven patients were screened for eligibility criteria. Of those, 160 patients were included in this study, with a mean age of 7.2±4.2 years old; 58.2% were boys, taking a mean of 3.0±1.3 drugs, and the most frequent primary diagnosis presented were leukemias (46.9%) and malignant bone tumors (12.5%). One hundred and twenty discrepancies were identified, of which 92.0% were unintentional discrepancies. Among them, 72.7% classified as omission, followed by frequency and/or number of units of dosage form and/or total daily dose (16.2%), duration or length of therapy (7.2%), and drug duplication (3.9%). Ondansetron (37.3%) was the drug more involved in these discrepancies. Conclusion: This study presented high unintentional discrepancies between the updated medication list and the medical prescription in pediatric patients with cancer, most of which classified such as inclusion. Our findings showed the importance of the clinical pharmacist to minimize medication errors in these patients.